STRUCTURE AND EVOLUTION OF THE LESNAYA THRUST (NORTHERN KAMCHATKA) - Shapiro M.N.; Solovyov A.V. (My University, 2001)
The Lesnaya thrust on the Kamchatka isthmus is part of the collisional suture separating the Upper Cretaceous complexes of the Achaivayam-Valaginskiy paleoarc from coeval terrigenous complexes of NE Asia continental slope. The formation of the modern structure of the suture zone was initiated by deep thrusts in an allochthonous complex, whose lower plates are made up of green schists and ultrabasite-gabbro bodies. Blastomylonite zones with asymmetric folds were forming at the boundary of the plates; the folds indicated movement of the plates from east to west. Deformations occured in conditions of extreme warming-up of the crust inherited from the active stage of the arc development. Subsequently these plates were moved onto the surface, and together with the shallower parts of the allochthon were overthrust onto the subaqueous margin of the continent overlain by terrigenous flysch. The autochthonous complex is crumpled into an intricate system of small, differently oriented folds reflecting deformation of the plastic layered thick sequence under conditions of slight predominance of sublatitudinal compression. Low temperature mylonites with pronounced Riedel structures indicating displacement of the allochthon to the northeast parallel to the thrust front are developed along the slip plane. The most plausible explanation of such kinematics is a change of thrusts by NE strike-slip faults at final stages of collision.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая